(untitled) (Journal of the College of Basic Education, 2022)
Designing instructional training plans to develop emotional intelligence in the school theater material. Measurement of students’ achievement in school theater material. measuring the emotional intelligence of the students of the Institute of Fine Arts. o verify the research objective, the researcher presented the following hypotheses The first hypothesis: - There are no statistically significant differences at the level of (0,05) between the average scores of the experimental group on the measure of emotional intelligence in the pre-test the second hypothesis: No significant differences at the level of significance (0,05) The experimental group and the mean scores of the control group students on the emotional intelligence scale in the post-test. The third hypothesis: There are no statistically significant differences at the level of (0,05) between the average scores of the experimental group students on the cognitive achievement test in the tribal tests The researcher identified the topics to be studied during the experiment in six subjects. The researcher formulated the behavioral goals. The researcher prepared the study plans and presented them to the students. Also, the experts and arbitrators have made the necessary adjustments and in light of that, they are ready for implementation. To measure the students’ achievement of the two groups, a test was conducted consisting of (25) The correct answer to the images) and verified the researcher’s honesty and stability and the strength of discrimination and the difficulties of the paragraphs, and prepare the test performance skill and be of (25) paragraph was confirmed the charity and the calculation of stability, and after the end of the experiment was applied cognitive and skill test on the students and after the analysis of the results and processed The researcher reached a number of conclusions The effectiveness and effectiveness of learning in the group in raising the level of achievement and delivery of skills to students The use of group learning is motivated to motivate students to reach the highest levels of achievemen The development of the learning of the team skills of thinking and the ability to analyze situations and solve problems Recommendations 1-the importance of relying on the strategy of learning in the field 2-the need to pay attention to strategies that will develop the mental and emotional abilities of students. 3-Teacher training on the use of the strategy of learning and the provision of the potential crisis to implement Suggestioon: 1- the impact of the strategy of learning in the control of the individual in the subject of aesthetic education impact of theater recruitment to develop sympathy in the art history. A comparative study of emotional intelligence in the students of the Institute of Fine Arts and students of the Institute of Fine Arts